Tinjauan Teologis dan Dampak Perceraian Menurut Matius 19:6 - Benny Andreson Situmorang; Dina Sembiring (IAKN Tarutung, 2022)
AbstractDivorce is a decision that is very contrary to God's will. But it is often the final decision in solving heavy and complicated problems in a marriage. This has also often been experienced by Christian families. That is why it is very important to understand the Word of God in Matthew 19:6 saying: “So then, they are no longer two but one flesh. Therefore what God has joined together, let not man separate.